RANCANG BANGUN SISTEM INFORMASI E-STORE OFFICE SUPLAYS DAN JASA LOGISTIK BERBASIS ANDROID PADA PT. GARFI INDOTAMA KARYA - Oematan, Vemilia; Kristiana, Titin (Jurnal Ilmiah Sistem Informasi, 2023)
This study aims to design and implement an E-Store information system that involves selling office supplies products and logistics services online at PT. Garfi Indotama Karya. This system is designed to be website-based to improve efficiency and affordability of service for customers. The system development method used is a web-based system design method that involves needs analysis, design, development, and implementation. The main functions of the system include the process of ordering office supplies products, stock management, and providing logistics services. Users can access this system easily through a responsive web interface. This research is expected to make a positive contribution in improving the operational effectiveness of PT. Garfi Indotama Karya and provide a better shopping experience for customers through an E-Store platform that is integrated with logistics services